POTENSI HASIL TIGA BELAS GALUR JAGUNG HIBRIDA SILANG TUNGGAL RAKITAN POLITEKNIK NEGERI LAMPUNG - Kartahadimaja, J. (Politeknik Negeri Lampung., 2010)
Hybrid corn is a first generation (F1) from the cross between two or more inbred line. Hybrid maize seed produced in Indonesia by BISI, PT.Du Pont Indonesia, and Syngentha. Inbred line as seed imported from abroad. In Indonesia the company only produce F1 hybrid seed corn. The problem for Indonesia is a very large dependency needs seed hybrid corn to foreign countries.Polinela current tread olready up 13 single-cross maize hybrid with inbred line the assembly itself in Polinela. Research aims to find the groove single cross corn hybrids that have superior characters in the quality and quantity.Research conducted in Polinela, Maret 2009 until July 2009. Research conducted with Randomize Completly Block Design (RCBD) as the treatment were 13 single cross maize hybrid assembly Polinela. Use as a benchmark Pioneer 23 (P-23), all treatment repeated three times. To know the differences between the treatment then continued with Least Significant Different (LSD) on stage 5%. Results of the research potential of 13 single cross hybrid there are (1) Generally assembly Polinela hybrid have caracteristics not significant rather than P-23, (2) Two assembly Polinela hybrid that has the potential of higher than P-23, that is hybrid C (PL. 401xPL. 201) and Hybrid K (PL. 20xPL.401). Keywords: Hybrid corn, inbred line, single cross